2021
DOI: 10.1111/sed.12940
|View full text |Cite
|
Sign up to set email alerts
|

Late Holocene stratigraphic evolution and sedimentary facies of an active to abandoned tide‐dominated distributary channel and its mouth bar

Abstract: To better understand the sedimentary facies of tide-dominated deltas, a core dataset from the Ba Lai palaeochannel in the Mekong River Delta was obtained and studied. Nine sedimentary facies were identified and interpreted as representing the Late Holocene evolution of the Ba Lai palaeochannel, including its pre-abandonment and post-abandonment phases, as well as pre-channel phases. The channel formed at 2.6 ka as a distributary channel connected to the deltaic network and was abruptly abandoned and rapidly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 78 publications
(142 reference statements)
1
3
0
Order By: Relevance
“…By contrast, Brown and Hale (2021) report that in deposits of the modern tide‐dominated Ganges–Brahmaputra delta, regular reworking by tides obliterates any potential signatures of seasonal riverine variations. Similar observations were also made by Gugliotta et al (2022) for the tide‐dominated and wave‐dominated Mekong delta, where the monsoonal signature is thoroughly overprinted by tidal processes in the tide‐dominated part of the system. The deposits of modern wave‐dominated deltas and strandplains also show more intense marine reworking and reduced preservation of interbedded patterns, although some of these beds are present locally (Khan et al, 2021; Qiaola et al, 2022; Tamura et al, 2008).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…By contrast, Brown and Hale (2021) report that in deposits of the modern tide‐dominated Ganges–Brahmaputra delta, regular reworking by tides obliterates any potential signatures of seasonal riverine variations. Similar observations were also made by Gugliotta et al (2022) for the tide‐dominated and wave‐dominated Mekong delta, where the monsoonal signature is thoroughly overprinted by tidal processes in the tide‐dominated part of the system. The deposits of modern wave‐dominated deltas and strandplains also show more intense marine reworking and reduced preservation of interbedded patterns, although some of these beds are present locally (Khan et al, 2021; Qiaola et al, 2022; Tamura et al, 2008).…”
Section: Discussionsupporting
confidence: 86%
“…It was also reported that the palaeoseaward‐dipping bedding of the interpreted tidal bars was different from the ones of modern tidal bars, and instead were more similar to the mouth bars of fluvial‐dominated deltas or inlet deltas (see p. 503 of Willis & Gabel, 2001). Furthermore, the high sandstone–mudstone ratios in the Sego Sandstone contrast with the much lower sand–mud ratios the typify the deposits of modern tide or mixed tide‐dominated and wave‐dominated deltas, such as the Mekong River delta (Gugliotta et al, 2017, 2019, 2022), which has been proposed as an analogue for the studied units (Legler et al, 2014; van Cappelle et al, 2016). The reinterpretation of the Sego Sandstone/Buck Tongue system as a mixed process, fluvial‐dominated delta would better explain the accretion and palaeocurrent patterns observed and would reconcile the discrepancy regarding the sand–mud ratios.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations